Interface bonding properties of new and old concrete: A review - Liu, He; Zou, Haonan; Zhang, Jingyi; Zhang, Ji; Tang, Yu; Zhang, Jian; Guo, Ying; Xiao, Jingyu (Frontiers in Materials, 2024)
The bonding performance between new and old concrete affects the reliability and service life of the repair structure. However, the bonding interface is complex and has many influencing factors, so selecting appropriate repair materials and evaluation methods for repair structures under different service environments is important. This paper presents a comprehensive overview of the factors that influence bonding properties. These include the choice of repair materials, the condition of the existing concrete, the type of interfacial agents used, the service environment, and the testing methods employed. The paper concludes by examining the challenges and opportunities in developing interface bonding properties to provide insights and research directions for future theoretical analysis and experimental research.